2014
DOI: 10.1186/1475-2875-13-282
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of community-based systems for the surveillance of day three-positive Plasmodium falciparum cases in Western Cambodia

Abstract: BackgroundDelayed clearance of Plasmodium falciparum parasites is used as an operational indicator of potential artemisinin resistance. Effective community-based systems to detect P. falciparum cases remaining positive 72 hours after initiating treatment would be valuable for guiding case follow-up in areas of known resistance risk and for detecting areas of emerging resistance.MethodsSystems incorporating existing networks of village malaria workers (VMWs) to monitor day three-positive P. falciparum cases wer… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
24
0

Year Published

2014
2014
2020
2020

Publication Types

Select...
6
1
1

Relationship

2
6

Authors

Journals

citations
Cited by 16 publications
(27 citation statements)
references
References 29 publications
(22 reference statements)
0
24
0
Order By: Relevance
“…Each of the 114 villages has two VMWs who are trained to diagnose malaria infections using rapid diagnostic tests (RDT), and to provide treatment according to national guidelines. VMWs routinely collect blood films and filter paper blood spots and send a short message service (SMS) to alert the public health facility and the national malaria programme when a new malaria case is identified [ 30 ]. At the initial time of this study, the first-line treatment in Pailin was atovaquone-proguanil (AP, Malarone, GlaxoSmithKline) and then shifted to dihydroartemisinin–piperaquine (DHA–PQP) towards the middle of the study until the end.…”
Section: Methodsmentioning
confidence: 99%
“…Each of the 114 villages has two VMWs who are trained to diagnose malaria infections using rapid diagnostic tests (RDT), and to provide treatment according to national guidelines. VMWs routinely collect blood films and filter paper blood spots and send a short message service (SMS) to alert the public health facility and the national malaria programme when a new malaria case is identified [ 30 ]. At the initial time of this study, the first-line treatment in Pailin was atovaquone-proguanil (AP, Malarone, GlaxoSmithKline) and then shifted to dihydroartemisinin–piperaquine (DHA–PQP) towards the middle of the study until the end.…”
Section: Methodsmentioning
confidence: 99%
“…However, following the widespread resistance to CQ and other antimalarial drugs, P.falciparum parasites produced resistance to DHA-PIP too, shortly after it was widely used in Southeast Asia, initially showing prolonged parasite clearance time (PCT) and subsequently treatment failures as the partner drug also failed [11][12][13][14][15][16][17][18][19][20][21][22][23][24]. The epicenter of the resistance was Cambodia where CQ resistance had also been first emerged [1][2][11][12][13][14][15][16][17][18][19][20]. This resistance rapidly spread to other neighboring countries, such as Thailand, Vietnam, laos, PDR and Myanmar, which all are part of the Greater Mekong sub-region (GMS) countries [25][26][27][28].…”
mentioning
confidence: 99%
“…A few studies revealed that the decreasing efficiency of DHA-PIP in the GMS involved resistance to both DHA and PIP [11][12][13][14][15][16][17][18][19][20][21]. Based on the single nucleotide polymorphisms (SNPs) examination and correction analysis with genomic tools, mutant K13-propeller alleles, such as C580Y, R539T, Y493H, I543T, were verified to be correlated with the spread of resistance in west Cambodia and other GMS countries [29].…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…[1][2][3][4] In 2011, Cambodia committed itself to eliminating malaria by 2025. This goal may be challenged by the emergence of multidrug-resistant, including artemisinin-resistant Plasmodium falciparum (ART-R) [5][6][7][8] and, now, the demise of dihydroartemisinin-piperaquine.…”
Section: Introductionmentioning
confidence: 99%